Research and design of LED driver - Zhang, Xiao (2018)
LED is a mature type of light source, which has many advantages compared with traditional incandescent and fluorescent: small size, low power consumption, long lifetime, high brightness, good dimming, fast response, reliable and durable , safety and environmental protection and so on. Now LED has been applied in many fields, such as traffic lights, car lights, LED backlight and indoor lighting. So the study of LED is both meaningful and necessary.